(untitled) (CAHIERS MAGELLANES-NS, 2025)
Background: Burnout syndrome, characterized by emotional exhaustion and reduced professional efficacy, is increasingly recognized as a significant concern among healthcare workers. With the demanding nature of their roles, medical professionals in Saudi Arabia frequently report high levels of emotional distress, suggesting a pressing need for targeted interventions. This study aimed to assess the frequency and intensity of burnout among healthcare workers in Saudi Arabia and to explore its association with various coping strategies. Methods: A descriptive cross-sectional study was conducted between July and November 2024, involving 498 healthcare professionals across multiple facilities in Saudi Arabia. Participants completed the Maslach Burnout Inventory (MBI) to evaluate emotional exhaustion, depersonalization, and personal accomplishment. Demographic data and work-related factors were also collected and analyzed. Results: The findings indicated that 35.4% of respondents reported experiencing emotional exhaustion frequently, while 29.3% displayed high levels of burnout. Emotional distress was prevalent, with 28.9% of participants acknowledging daily stress from patient interactions. Depersonalization was noted among those implying feelings of emotional detachment; nearly half of respondents reported rarely experiencing such detachment. Statistical analyses revealed significant associations between burnout levels and demographic factors such as age, marital status, and income satisfaction. Conclusion: The study highlights a critical prevalence of burnout among healthcare workers in Saudi Arabia, revealing significant emotional exhaustion and stress linked to their professional roles. Given the potential detrimental effects on personal well-being and patient care, urgent implementation of organizational strategies to address burnout is essential. Efforts should focus on enhancing supportive work environments, promoting coping strategies, and addressing systemic issues contributing to workplace stress.